METHODS OF INCREASING THE LEVEL OF COGNITIVE ACTIVITY OF STUDENTS WHEN IMPLEMENTING MIXED FORMS IN MEDICAL EDUCATION - Malokhat O. Komilova (Central Asian Journal of Medicine, 2022)
The article reveals the use of blended forms of education in a seminar, which is relevant today, since in the modern world it is very important to use various forms of blended learning. The paper analyzes the literature and Internet sources, analyzes the possibilities of forms of blended learning in the study of pedagogical disciplines. The problem, goal, research objectives, methods for its implementation are determined. At the same stage, a survey was conducted among students of the Tashkent Medical Academy. In the article, when studying the forms of blended learning at the stage of collecting empirical data, empirical methods were carried out: observation and conversations with students, questioning students; and theoretical methods: analysis, synthesis, design and modeling of lessons on "Educational technologies" based on the technology of blended (hybrid) learning. Using the "Change of working areas" method, it is possible to achieve the goal of using blended forms of education in medical education, which assesses the level of cognitive activity of students in a medical university. The experiment involves students of the 3rd year of biomedical science and the 4th year of the faculty of vocational education (general medicine) on the subject "Educational technologies", in which a comparative analysis was carried out in the first and fifth lessons. The object of the research is the process of teaching forms of blended learning in a medical university in the study of pedagogical disciplines. The results of the study confirm the assumption that the educational process in distance form will be effective when using forms of blended learning, modern Internet resources, services, video hosting sites, platforms that are presented in this work. The relevance of the article lies in the fact that it is necessary to consider blended learning as a tool for the implementation of a remote form of work, which opens up prospects for further research in the application of various forms of this technology at various levels and stages of education in the process of pedagogical training during the period of potential quarantine measures. Studying the problem of using forms of blended learning in these conditions, we can conclude that it is necessary to achieve the systematic use of various forms of blended learning in the classroom, the perception of the teacher not as a bearer of knowledge and a controlling subject of knowledge, but as a coordinator, organizer of independent information activities; to learn cooperation, the use of group, collective individual forms of work, where students cease to be passive participants in the educational process.